1988
DOI: 10.1029/ja093ia09p09804
|View full text |Cite
|
Sign up to set email alerts
|

IMF By dependence of region 1 Birkeland currents near noon

Abstract: We have conducted a statistical study of large‐scale Birkeland currents, hot plasma, and the By component of the interplanetary magnetic field. Forty‐eight Viking orbits from July 19, 1986, to September 2, 1986, were used in the study during a time period when the 3‐RE geocentric apogee was located near the dayside high‐latitude region usually associated with the polar cusp. We first compared the location of magnetosheathlike electrons to the region 1 and “traditional cusp” Birkeland current systems near noon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
100
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 35 publications
19
100
0
Order By: Relevance
“…The same was true of the models of the corresponding patterns of ionospheric (Friis-Christensen et al, 1985) and field-aligned (Iijima et al, 1978;Erlandson et al, 1988) currents.…”
Section: Introductionmentioning
confidence: 66%
“…The same was true of the models of the corresponding patterns of ionospheric (Friis-Christensen et al, 1985) and field-aligned (Iijima et al, 1978;Erlandson et al, 1988) currents.…”
Section: Introductionmentioning
confidence: 66%
“…Their (R0, R1) current pair can be regarded as (R0, v-R1) in our terminology, because the intensities of R0 and v-R1 are the same; in their events the (c-R1, R2) pair was presumably nonexistent. Some papers suggested that there is no R2 in the midday sector (Iijima and Potemra, 1978;Erlandson et al, 1988) and it is interesting to note that the midday R1 may be constructed by v-R1 only.…”
Section: Discussionmentioning
confidence: 99%
“…The polarity of the R0 current depends on the B Y component of the IMF, being upwards (downwards) in the northern hemisphere for B Y > 0 (B Y < 0) and opposite in the southern hemisphere (Wilhjelm et al 1978;Erlandson et al 1988;Papitashvili et al 2002;. This current system is associated with east-west flows in the dayside polar cap caused by magnetic tension forces on newlyreconnected field lines.…”
Section: Magnetospheric Current Systemsmentioning
confidence: 99%